Hearing loss and its relation to cognition in Indian cohort: A behavioral and neuroimaging study - Deepashri Agrawal; Palash Kumar Malo; Sadhana Singh; Thomas Gregor Issac (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2025)
Abstract INTRODUCTION Hearing loss (HL) is an unexplored modifiable risk factor that impacts 41% of the Indian population. This study aimed to determine the prevalence of HL, investigate the association between HL and cognitive impairment in older adults, and assess neuronal structures involved in HL and cognitive impairment using behavioral and magnetic resonance imaging (MRI). METHODS This study assessed 589 individuals aged 45 and above using HearCheck handheld audiometry, cognitive testing, and MRI. RESULTS Participants with HL are 1.69 times more likely to experience cognitive impairment compared to those without HL. Neuroimaging revealed significantly less gray matter in various temporal and hippocampal regions in individuals with HL and cognitive impairment as compared with normal hearing and normal cognition. DISCUSSION These findings underscore the importance of exploring the link between sensory impairments, specifically HL, and cognitive impairment, emphasizing the need for preventive strategies in diverse populations. Highlights A large urban cohort provides insights into hearing and cognitive function. Hearing loss (HL) is associated with a 69% higher likelihood of cognitive impairment. Magnetic resonance imaging (MRI) reveals reduced gray matter (GM) loss in individuals with HL. Comprehensive cognitive and hearing evaluations strengthen findings. Findings align with sensory deprivation and shared risk factor hypotheses.